O-Antigen Biosynthesis: Hitting the Sweet Spot for a Q Fever Vaccine - Cross, Alice; Roy, Sumita; Norville, Isobel; Rezjek, Martin; Ivanova, Irina; Nepogodiev, Sergey; Field, Rob; Prior, Joann; Hamer, Nicholas (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.Coxiella burnetii, the causative agent of Q fever, is a pathogen with a worldwide distribution. Biological material shed from ruminant infections contaminates dirt and dust, which can cause infection on inhalation. Humans generally present with flu-like symptoms, however, patients can develop life-changing maladies such as hepatitis, chronic fatigue, and endocarditis. Q fever was initially identified as a military problem when thousands were affected during WWI. More recently, Q fever has been recognised as a problem in UK troops returning from Afghanistan. C. burnetii is classified as a CDC category B bioterrorism agent, the second highest category, yet there is no Q fever vaccine licensed in the UK/EU/US. For C. burnetii, the lipopolysaccharide (LPS) is the main determinant of virulence, and many of the most effective modern vaccines target such sugar structures. Furthermore, the sugars that comprise the C. burnetii LPS are highly unusual, making this the primary target for vaccine development. In order to facilitate production of a subunit vaccine, focus is on elucidating the pathways for biosynthesis of two very rare sugars, virenose and dihydrohydroxystreptose (DHHS). Therefore in addition to providing the basis for a novel Q fever vaccine, for livestock and humans, this project will highlight novel biochemistry.
Keywords: 'O-Antigen'; 'Coxiella burnetii'; 'Vaccine'; 'DSDS17 poster'; 'DSDS17'; 'Biochemistry'